Risk factors for malnutrition among preschool children in rural Karnataka: a case-control study - Ansuya; Baby S. Nayak; B. Unnikrishnan; Anice George; Shashidhara Y. N.; Suneel C. Mundkur; Vasudev Guddattu (BMC, 2018)
Abstract Background The prevalence of malnutrition among children in developing countries is very high. As a step towards reducing the prevalence of malnutrition, there is a need to identify the important determinants of malnutrition in the specific population so that preventive and control measures can be implemented. The objective of the study is to determine the risk factors for malnutrition among preschool children in Rural Karnataka, South India. Methods A case-control study was carried out among preschool children, aged between three to six years, attending the Anganwadi centers and their mothers' in Udupi district of Karnataka, India. A total of 570 children (190 cases and 380 controls) were selected by multistage cluster sampling technique. A semi-structured risk factors questionnaire was used to identify the risk factors for malnutrition among children. Results The majority (45.8 and 45.5%) of the children in the study were in the age group of 3.0 to 4.0 years in case and control groups respectively. There was a slight preponderance of illiterate parents among cases in comparison to the controls. Largely, 87.4% of the children belonged to poor socio-economic status in the case groups compared to 82.4% in the control group. After adjusting for the confounders, underweight was significantly associated with socio-economic status of the parents (aOR: 2.05, 95% CI: 1.06, 3.96), birth weight < 2000 g (aOR: 25, 95% CI: 0.10, 0.59), recurrent diarrhoea (aOR: 2.74, 95% CI: 1.56, 4.83), recurrent cold and cough (aOR: 3.88, 95% CI: 1.96, 7.67), worm infestation (aOR: 2.0, 95% CI: 1.19, 3.38) and prelacteal feed given (aOR: 3.64, 95% CI: 2.27, 5.86). Conclusion Parental education, childhood illness, short birth interval, open defecation, type of weaning and complimentary food given to children were some of the significant determinants of underweight that were found in the study. Information, Education and Communication (IEC) campaigns alleviating food habits and taboos and promoting birth spacing is the need of the hour for preventing the occurrence of undernutrition among preschool children.